Math skills and microstructure of the middle longitudinal fasciculus: A developmental investigation. - Irina Buianova; Asya Istomina; Andrei Manzhurtsev; Maxim Ublinskiy; Victor Karpychev; Marie Arsalidou (PLoS ONE)
Functional neuroimaging studies have identified distributed brain networks involved in arithmetic problem-solving. However, it is still poorly understood to what extent microstructural properties of the underlying white matter contribute to mathematical performance. We investigate microstructural characteristics of one of the least studied white matter tracts, the bilateral middle longitudinal fasciculus (MdLF), reconstructed from diffusion-weighted MRI data, and their relations with mathematical performance in arithmetic tasks of varying complexity, in 56 individuals aged 10-29 years (22 children: 10-13 years; 20 adolescents: 14-17 years; 14 adults: 18-29 years). We identify group differences in math performance and diffusivity measures. We highlight linear relations with age in left fractional anisotropy and right radial diffusivity, which can serve as developmental markers. Further, we document for the first time that diffusivity values in the right MdLF are significantly lower than in the left MdLF for all groups, suggesting hemispheric asymmetry. Importantly, associations between math performance in the right MdLF favoured easier tasks and in the left MdLF favoured harder tasks. This finding is a deviation from the classic hemisphere dominance hypothesis. We propose that the observed patterns may be explained by the right-left-right hemispheric dominance hypothesis proposed by a theory of cognitive development. Our results provide new insights into the microstructural properties of the MdLF and their role in mathematical ability, with implications for understanding brain-behaviour relations.